Analyze of Relationship Predisposing and Reinforcing Factors On The Completeness of Tetanus Toxoid Immunization In Pregnancy - Lucya Lede; Bagoes Widjanarko; Sri Achadi Nugraheni (JURNAL KEBIDANAN, 2021)
Tetanus Toxoid (TT) immunization for pregnant women is a crucial public health issue. This study aimed to identify the predisposing and reinforcing factors and their association with the completion of TT immunization for pregnant women. This mixed-method research included 50 pregnant women in their 2nd and 3rd trimesters who attend the Posyandu and three mother-and-child health (MHC) workers in Getasan Public Health Center. The predisposing factors include knowledge and attitude of the pregnant women and reinforcing spouse support and perception toward health workers. The result shows a significant correlation among predisposing and reinforcing factors with the completion of TT immunization. On the other hand, the MHC workers indicate loss of follow-up and maladministration, which further act on TT immunization among pregnant mothers. We suggest MHC workers strengthen the administration and education among pregnant women